Investigation of the Mechanisms and Experimental Verification of Yulin Formula in the Treatment of Diminished Ovarian Reserve via Network Pharmacology - Wang R; Zhao Y; Miao C; Chen Y; Ren N; Yang L; Cheng W; Zhang Q; Fang X (Dove Medical Press, 2023)
Ruye Wang,1,* Ying Zhao,2,* Chenyun Miao,3 Yun Chen,1 Ning Ren,1 Liuqin Yang,1 Wei Cheng,4 Qin Zhang,1,5 Xiaohong Fang1 1Department of TCM Gynecology, Hangzhou TCM Hospital of Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 2School of Public Health, Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 3School of Life Sciences, Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 4Department of Orthopedics, Hangzhou TCM Hospital of Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 5Research Institute of Women's Reproductive Health, Zhejiang Chinese Medical University, Hangzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Qin Zhang; Xiaohong Fang, Department of Medical TCM Gynecology, Hangzhou TCM Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310007, People's Republic of China, Email zhaqin01@163.com; fxh13527806@163.comPurpose: The aim of this study is to examine, using network pharmacology analysis and experimental validation, the pharmacological processes by which Yulin Formula (YLF) reduces cyclophosphamide-induced diminished ovarian reserve (DOR).Methods: First, information about the active components, associated targets, and related genes of YLF and DOR was gathered from open-access databases. The primary targets and pathways of YLF to reduce DOR were predicted using studies of functional enrichment from the Kyoto Encyclopedia of Genes and Genomes (KEGG), Gene Ontology (GO), and Protein-Protein Interaction (PPI) networks. Second, we built a cyclophosphamide-induced diminished ovarian reserve (DOR) rat model to verify the primary target proteins implicated in the predicted signaling pathway to explore the mechanism of improve ovarian function of YLF.Results: 98 targets met the targets of the 82 active ingredients in YLF and DOR after searching the intersection of the active ingredient targets and DOR targets. Fourteen targets, including AKT and Caspase-3 among others, were hub targets, according to the PPI network study. The PI3K/AKT pathway was revealed to be enriched by numerous targets by the GO and KEGG enrichment studies, and it was used as a target for in vivo validation. Animal studies showed that YLF administration not only reduced the number of atretic follicles, the proportion of TUNEL-positive ovarian cells, the rate of apoptosis of granulosa cells (GCs) and the proportion of abnormal mitochondria in DOR rats, but also reversed the high expression of Caspase-3, Caspase-9, BAX, cytochrome C, PI3K and P-AKT, improving the ovarian reserve in cyclophosphamide (CTX)-induced DOR rats.Conclusion: Our research results predicted the active ingredients and potential targets of YLF-interfering DOR by an integrated network pharmacology approach, and experimentally validated some key target proteins participated in the predicted signaling pathway. A more comprehensive understanding of the pharmacological mechanism of YLF for DOR treatment was obtained.Keywords: diminished ovarian reserve, Yulin Formula, network pharmacology, pharmacological mechanisms, apoptosis, PI3K/AKT